Dolphin-complab: a virtual compilers laboratory - Matos, Paulo (2003)
DOLPHIN-COMPLAB is a project to implement a virtual laboratory containing all the necessary features for the development of compilers and compiler components. It was conceived to supply an environment for assisted cooperative work, based on the web technologies, and to be used by teams of investigators, developers or simple teacher/students.